Assemblages of excess and pleasures: The sociosexual uses of online and chemical technologies among men who have sex with men. (6th October 2021) - Numer, Matthew; Holmes, Dave; Hammond, Chad; Joy, Phillip; Sinno, Jad
Abstract: Chemicals have penetrated everyday lives of men who have sex with men as never before, along with new online and mobile technologies used to seek pleasures and connections. Poststructuralist (including queer ) explorations of these new intensities show how bodies exist in the form of (political) surfaces able to connect with other bodies and with other objects where they may find/create a function (e.g., reproduce or disrupt hegemonies). This federally funded netnographic study explored how a variety of chemicals such as recreational drugs, pharmaceuticals and steroids are contributing to the construction of gay, bisexual and other men having sex with men (GBMSM) communities and their interactions with idealized masculinities in the age of increasing technology. Five major thematic categories emerged from our analysis: (1) assembling bodies and technologies, (2) becoming orgiastic, (3) experiencing stigma, (4) becoming machinic and (5) negotiating practices. Our analysis explores how and why GBMSM pursue excesses of pleasure and connection through the assemblages they make with sexualized drug use, online platforms and other men.